Repo Market Effects of the Term Securities Lending Facility - Fleming, Michael J; Hrung, Warren B; Keane, Frank M (American Economic Review, 2010)
Repo Market Effects of the Term Securities Lending Facility by Michael J. Fleming, Warren B. Hrung and Frank M. Keane. Published in volume 100, issue 2, pages 591-96 of American Economic Review, May 2010